(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Sleep plays essential role in restoring both cognitive and physical performance, up to now its particular impact within military populations remains unknown. Military cadets often go through demanding schedules and high-stress environments that can compromise both sleep quality and duration. Research has shown that insufficient or poor-quality sleep is associated with declined physical performance, affecting endurance, strength, and coordination. Yet, Maximum existing studies have focused on the general population, offering little awareness into the unique challenges faced by cadets. The strict nature of military training may increase the bad effects of sleep deprivation. Understanding the connection between sleep and performance in this context is crucial for improving training outcomes and decreasing the risk of injury. This study pursues to assess how variations in sleep quality and duration influence physical performance among military cadets. The results could notify the development of targeted strategies to magnify sleep hygiene and overall readiness in military training programs. Objective: Assess the impact of sleep quality and duration on physical performance in military cadets, inspect how inequality in sleep patterns affect physical fitness levels and overall performance. Methodology: A cross-sectional study was conducted involving military cadets to Inspect the Connection between sleep and physical performance. A total of 169 military cadets were included in the study as the sample size. Participants completed the Pittsburgh Sleep Quality Index (PSQI) and the Sleep Hygiene Index to assess their sleep quality and duration. Physical activity levels were judged using the International Physical Activity Questionnaire (IPAQ). Statistical analyses were performed by SPSS version 29 to Find out the Connection between sleep variables and physical performance effects. The data was analyzed by using statistical technique chi square test. Result: The results of the study demonstrated a statistically significant relationship between sleep patterns and physical performance among cadets. The correlation analysis revealed that poor sleep hygiene and quality—measured using SHI and PSQI—were positively linked with decreased physical activity levels measured via IPAQ. The highest correlation was noted between stress before bed and poor sleep hygiene (73.3%), and between trouble staying awake and poor sleep quality (58%). A chi-square test confirmed these relationships were statistically significant, as p-values for all hypotheses were less than 0.05, leading to the rejection of the null hypothesis. This indicates a meaningful association between sleep quality, duration, and physical performance. The strongest associations were observed in the age group 21–23 years, non-smokers, and unmarried cadets, with the majority showing poor sleep quality and high physical activity. The findings emphasize the need to improve sleep hygiene to enhance physical performance among military cadets. Conclusion: This study comes to the conclusion that military cadets’ physical performance is adversely affected by both inadequate sleep duration and poor sleep quality. Reduced strength, endurance, reaction time, and recuperation—all essential components of military training and preparedness—were linked to sleep deprivation. The results highlight how crucial it is to incorporate regulated sleep schedules, environmental changes, and instruction about good sleep hygiene into military training programs. Specific sleep-related interventions may improve mental and physical function while lowering the risk of damage. To guarantee peak performance and operational efficacy in military environments, sleep should be seen as an essential part of cadet health, in addition to physical training and a healthy diet.